DIVINE KNOWLEDGE AT HARVARD AND YALE: FROM WILLIAM AMES TO JONATHAN EDWARDS - Fisk, Philip John (Jonathan Edwards studies, 2014)
This essay makes the case that a significant shift occurred in the conception of the doctrine of divine knowledge and freedom, in the line from William Ames (1576-1633), traced through Van Mastricht, Heereboord, and Morton, to Edwards, marked by a neglect, intentional or otherwise, of technical terms used by post-Reformation scholastic authors. The study begins with the exchange of arguments in Ames’s Scholastic reply to the Remonstrant Nicolaus Grevinchovius (1615) and the latter’s Theological treatise (1615). The essay also examines a manuscript copy of Charles Morton’s "Pneumaticks," and claims that the evidence from the flyleaf shows that this student notebook came into the possession of Elisha Williams, Edwards’s tutor at Wethersfield. Moreover, evidence shows that the text is a translation of Heereboord’s "Pneumatics" and that a few crucial passages have been mistranslated, evidencing the shift that occurred in the understanding and use of technical terms. The essay will then examine the use and development by Van Mastricht and Edwards, in the latter’s Freedom of Will, of the well-known formula of Boethius (480-524) regarding the unchanging ever-presentness of God, as well as Edwards’s (1743) "Controversies" Notebook (WJE Online Vol. 27), on "Predestination." Finally, select Harvard and Yale commencement broadside theses and quaestiones show the influence of Ames and that technical distinctions on structured conceptual planes of divine knowledge were being made in the schools, which are necessary to understanding the Reformed doctrine of divine freedom. It appears that Edwards, however, rested his published arguments on Boethius’s single conceptual plane of divine knowledge rather than appropriating a post-Reformation development of a twofold conceptual scheme.